Electrochemical magneto immunosensor based on endogenous β-galactosidase enzyme to determine enterotoxicogenic Escherichia coli F4 (K88) in swine feces using square wave voltammetry - Tarditto, Lorena Viviana (2017)
Diseases caused by enterotoxicogenic Escherichia coli F4 (K88) (ETEC F4) are a problem in swine production establishments. Due to the high rate of mortality and morbidity of E. coli infections, a rapid and accurate diagnosis is important in order to choose an appropriate treatment to reduce the economic impact. Therefore, an electrochemical magneto-immunosensor (EMI) was developed to detect and quantify ETEC F4 in swine feces samples through a direct non-competitive immunoassay. ETEC F4 was selectively captured by immunomagnetic separation. The detection principle was based on the activity of β-galactosidase endogenous enzyme (β-gal), which hydrolyses the p-aminophenyl-β-D-galactopyranoside (p-APG) producing p-aminophenol (p-AP), which was oxidized on a carbon screen printed electrode (CSPE) using square wave voltammetry (SWV). All parameters related to construction and electrochemical responses were optimized. The total analysis time to quantify ETEC F4 using the EMI was less than 2 h and the limit of detection (LOD) was 33 CFU mL−1. The perceptual relative error (%Er) was 20%. The magneto-immunosensor was validated versus conventional method of culture and plate count, obtaining a very good agreement. The EMI is simple, fast and economical to detect and quantify ETEC F4 in swine feces samples, being thus a valuable tool in swine production.